Commodity risk assessment of Robinia pseudoacacia plants from Turkey - EFSA Panel on Plant Health (PLH); Claude Bragard; Katharina Dehnen‐Schmutz; Francesco Di Serio; Paolo Gonthier; Marie‐Agnès Jacques; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A Navas‐Cortes; et al. (EFSA Journal, 2021)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation EU/2018/2019 as ‘High risk plants, plant products and other objects’. This Scientific Opinion covers plant health risks posed by bare rooted and potted plants of Robinia pseudoacacia that are imported from Turkey, taking into account the available scientific information, including the technical information provided by the Turkish NPPO. The relevance of any pest for this opinion was based on evidence following defined criteria. Three species, the EU‐quarantine pests Anoplophora chinensis and Lopholeucapsis japonica, and the EU non‐regulated pest Pochazia shantungensis fulfilled all relevant criteria and were selected for further evaluation. For these pests, the risk mitigation measures proposed in the technical dossier from Turkey were evaluated taking into account the possible limiting factors. For these pests, an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The estimated degree of pest freedom varies among the pests evaluated, with L. japonica being the pest most frequently expected on the imported plants. The Expert Knowledge Elicitation indicated, with 95% certainty, that between 9,521 and 10,000 plants per 10,000 would be free of L. japonica.